Changes in Distribution Patterns for Larimichthys polyactis in Response to Multiple Pressures in the Bohai Sea Over the Past Four Decades - Han, Qingpeng; Shan, Xiujuan; Jin, Xianshi; Gorfine, Harry; Chen, Yunlong; Su, Chengcheng (Frontiers in Marine Science, 2022)
Understanding patterns of change in the distribution of species among their critical habitats is important for analyzing population dynamics and adaptive responses to environmental shifts. We investigated spatio-temporal changes in small yellow croaker (Larimichthys polyactis) using eight alternative models fitted to data from bottom trawl surveys conducted in the Bohai Sea each spring (spawning period) and summer during 1982–2018. These models included different combinations of local sea temperature, fishing pressure, and individual climate index (i.e., North Pacific index, NPI, and West Pacific index, WPI) as explanatory variables. Selection of the most parsimonious model for each season was based on Akaike’s Information Criterion (AIC). The model with NPI as its only explanatory variable was used as a base case for pre-analysis. In spring, a spatio-temporal model with sea temperature as a quadratic effect, plus the spatially varying effects of a climate index and fishing pressure was selected, as the AIC value of this model was reduced by 41.491 compared to the base case model without these effects. In the summer after spawning, the spatio-temporal model with WPI as a climate index covariate lagged by 1-year best explained the spatio-temporal distribution patterns of the stock. The results suggested that small yellow croaker populations significantly decreased in biomass in the Bohai Sea over the study period. A statistically significant northeastward shift in the center of gravity (COG) and a contraction in the distribution range occurred in summer throughout the study period (p<0.05). During the spring sequence (1993–2018), a statistically significant northeastward shift in the COG was also found (p<0.05). Our results showed that biomass-density hotspots of small yellow croaker in both seasons have shrunk or disappeared in recent years. Overall, these findings suggest that the spatio-temporal patterns of the populations in their spawning, feeding and nursery grounds have been influenced over the past 40 years by multiple pressures, and population density in the southwestern areas of the Bohai Sea declined faster and more drastically than in the northeastern areas. This study has important implications for developing targeted spatial conservation measures for small yellow croaker at various stages of its life history under different levels of stress.